2016
DOI: 10.1089/vio.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of Neighbors' Bystander Intervention in Intimate Partner Violence: A Concept Mapping Study

Abstract: Encouraging bystander intervention in intimate partner violence (IPV) against women is potentially an important method of reducing the prevalence of such violence in urban communities. Most existing research has been conducted on campuses and in relation to sexual violence among teens or young adults. Our understanding of which bystander behaviors are feasible is nascent, and our knowledge of which situational factors influence neighbors' self-reported willingness to intervene is underdeveloped. We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…In this regard, studies have demonstrated that neighbors can play a role in reporting abuses (Paquin, 1994 ). In addition, scholars have shown that informal actors (e.g., family, friends, and neighbors) are often approached by the victims of intimate partner violence because they are proximal and may be able to intervene before, during, and after the violent event (McCart, Smith, & Sawyer, 2010 ; Wee, Todd, Oshiro, Greene, & Frye, 2016 ). Related to this, the police attention to urban crimes may have diminished due to the need to enforce social distancing measures, thus partially countering the crime mitigating effect driven by looser social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies have demonstrated that neighbors can play a role in reporting abuses (Paquin, 1994 ). In addition, scholars have shown that informal actors (e.g., family, friends, and neighbors) are often approached by the victims of intimate partner violence because they are proximal and may be able to intervene before, during, and after the violent event (McCart, Smith, & Sawyer, 2010 ; Wee, Todd, Oshiro, Greene, & Frye, 2016 ). Related to this, the police attention to urban crimes may have diminished due to the need to enforce social distancing measures, thus partially countering the crime mitigating effect driven by looser social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have researched bystander action in community samples or from the viewpoint of victims (see Edwards et al, 2014; Wee et al, 2016; for exceptions). One exception (Frye et al, 2012) utilized concept mapping to determine how bystanders in urban neighborhoods prevented IPV and how effective residents perceived them to be.…”
Section: Bystander Interventionmentioning
confidence: 99%
“…Frye and colleagues (2012) documented bystander actions that participants in urban areas consider to be feasible and helpful in response to IPV, which includes calling the authorities, communicating with and engaging with neighbors, and offering help. Few studies have been conducted in rural areas, which may have different bystander patterns due to lower population density or less access to services (Edwards, Mattingly, Dixon, & Banyard, 2014; Wee, Todd, Oshiro, Greene, & Frye, 2016). There remains a broader lack of research on IPV in rural communities as well (DeKeseredy & Schwartz, 2009; Edwards, 2015).…”
mentioning
confidence: 99%
“…Willingness to intervene among those who are aware of IPVAW incidents is also relevant because victims tend to seek help among informal sources of help (friends, family, neighbors, coworkers, etc.) rather than formal sources such as the police ( Liang et al, 2005 ; Ansara and Hindin, 2010 ; McCart et al, 2010 ; McDonnell et al, 2011 ; Wee et al, 2016 ). Moreover, pro-intervention attitudes among these potential informal sources of help, when shared collectively, can contribute to shape local social norms that help deter this type of violence ( Wee et al, 2016 ; Voith, 2017 ; Powell and Webster, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…rather than formal sources such as the police ( Liang et al, 2005 ; Ansara and Hindin, 2010 ; McCart et al, 2010 ; McDonnell et al, 2011 ; Wee et al, 2016 ). Moreover, pro-intervention attitudes among these potential informal sources of help, when shared collectively, can contribute to shape local social norms that help deter this type of violence ( Wee et al, 2016 ; Voith, 2017 ; Powell and Webster, 2018 ). As Voith (2017 , p. 4) noted in her review, “the protective effects of pro-IPV-intervention norms in a community are twofold, in that community members will directly intervene if they witness IPV and perpetrators are less likely to continue the use of violence against their partners as a result of social pressure”.…”
Section: Introductionmentioning
confidence: 99%